KESIAPAN PEMERINTAH MENERAPKAN GREEN BANKING MELALUI POJK DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN BERDASARKAN HUKUM POSITIF DI INDONESIA - Agus Salim, Muhammad (Universitas Wiralodra, 2018)
The world of banking in Indonesia began to show its concern for environmental problems through various banking activities known as Green banking. Green banking is a program for a financial institution that makes sustainability a top priority in its business. Currently banks that have pledged green banking are required in OJK Regulation Number 51 / POJK.03 of 2017 concerning the Implementation of Sustainable Finance for Financial Service Institutions, Issuers and Public Companies to report on the results of implementing green banking. This writing discusses how the legal consequences of the implementation of green banking for banking business activities in Indonesia after the enactment of POJK Number 51 / POJK.03 in 2017 concerning the Implementation of Sustainable Finance for Financial Services Institutions, Issuers and Public Companies and how OJK conducts supervision. This study is a legal research using a normative juridical approach and descriptive analytical research specifications. The data used in this study are secondary data consisting of primary, secondary and tertiary legal materials. Data obtained through library studies and field research in the form of legislation, books, journals, and electronic media. The findings of this study are 2 (two) explanations namely First, the legal consequences of the implementation of green banking in banking business activities in Indonesia in realizing sustainable development have not been able to be carried out due to banks and financial services institutions both banks and non-banks do not yet have specific guidelines or references governing this green banking. Second, the obligation for banks that have pledged green banking is to provide insurance for the environment, considering that banking business activities also include insurance referring to Article 7 of the Banking Law. OJK has actually launched environmental insurance, but the Indonesian government has not responded to anything that has been conveyed by the OJK. The reason for the government according to the OJK informants is that the development of a little more would certainly damage the environment, so that environmental insurance is impossible in Indonesia.